Program Edukasi Bahaya Pewarna Dan Pemanis Pada Siswa Kelas X Kriya Kayu SMKN 4 Palangka Raya - Anatasya, Violina; Prastiti, Arini Eka Jaya; Triliyansi, Triliyansi (Kahayan : Jurnal Pengabdian Kepada Masyarakat, 2024)
The culinary industry in Indonesia, especially the snack and food sector, has great potential in creating job opportunities and attracting the interest of various consumer groups. However, the use of additives such as synthetic dyes and sweeteners in food is a major concern because it can pose health risks. These additives are used to improve the quality, taste, and visual appeal of food, but they can contain harmful substances such as borax, benzoic acid, sodium cyclamate, saccharin, and formalin that are often found in children's snacks. An education program on the dangers of synthetic dyes and sweeteners was carried out in class X of the Wood Craft department of SMK Negeri 4 Palangka Raya to increase students' understanding of the health risks of harmful chemicals in food. The counseling method involves conveying information about the types of chemicals, their health impacts, and tips for choosing safe food. Observations were made to see students' responses and participation during the activity. This educational program is expected to change students' consumption behavior, so that they are better able to maintain their health and spread awareness about the importance of healthy food in their environment